Bioecology Of Bear Cuscus (Ailurops ursinus) In The Batuputih Natural Tourism Park Area, Bitung City, North Sulawesi - Loha, Nonong Krisnawati; Tasirin, Johny Suwodjo; Saroinsong, Fabiola Baby (Sam Ratulangi University, 2024)
This research aims to identify the daily behavior, characteristics of food trees, and habitat characteristics of A.ursinus in the Batuputih Nature Tourism Park area, Bitung City, North Sulawesi. Data collection was carried out for one month (September - November 2023). Observation of daily behavior of A.ursinus using the Focal Animal Sampling method based on diurnal time. Observations of the characteristics of A.ursinus food trees were carried out every time A.ursinus carried out feeding behavior. Habitat characteristics are based on the structure and composition of the dominant species in the A.ursinus range. Daily behavior of A.ursinus observed included resting (88.8%), moving (5,8%), feeding (3,8%), grooming (1,1%), and social (0,6%). The diet of A.ursinus on Dracontomelon dao, Cananga odorata, Pterospermum javanicum, and Ficus benjamina as a whole (100%) comes from leaves. The remaining part of the fruit of Ficus variegata (5,6%) and the bark of the Garuga floribunda tree (0,9%) comes from the leaves. The average diameter of food trees was 65,5 ± 11,5 or ranging from 54,0-77,1 cm (α=5%, db=33), and the average tree height was 27,2 ± 2,8 or ranging between 24,4-30,0 m (α=5%, db=33). The highest Importance Values (INP) in A.ursinus habitat at tree level are Ficus benjamina (66,6%), Garuga floribunda (30,4%), and Cananga odorata, Palaqium obovatum (30,3%). Meanwhile, pole-level vegetation Phaleria capitata (40,8%), Diospyros sp. (37,7%), and Dracontomelon mangiferum (34,7%). These species play an important role in forming the home range of A.ursinus. Keywords: Bear cuscus (Ailurops ursinus), Bioecology, Wildlife. Abstrak Penelitian ini bertujuan untuk mengidentifikasi perilaku harian, karakteristik pohon pakan, dan karakteristik habitat A.ursinus di kawasan Taman Wisata Alam Batuputih, Kota Bitung, Sulawesi Utara. Pengambilan data dilaksanakan selama satu bulan (September- November 2023). Pengamatan perilaku harian A.ursinus menggunakan metode Focal Animal Sampling berdasarkan waktu diurnal. Pengamatan karakteristik pohon pakan dilakukan setiap kali A.ursinus melakukan perilaku makan. Karakteristik habitat berdasarkan struktur dan komposisi jenis-jenis dominan di jalur jelajah A.ursinus. Perilaku harian A.ursinus yang teramati meliputi, istirahat (88,8%), berpindah (5,8%), makan (3,8%), merawat diri (1,1%) dan sosial (0,6%). Diet A.ursinus pada Dracontomelon dao, Cananga odorata, Pterospermum javanicum dan Ficus benjamina secara keseluruhan (100%) berasal dari daun. Bagian buah Ficus variegata (5,6%) dan kulit pohon Garuga floribunda (0,9%) sisanya berasal dari daun. Rata-rata diameter pohon pakan adalah 65,5 ± 11,5 atau berkisar antara 54,0-77,1 cm (a=5%, db=33), dan rata-rata tinggi pohon adalah 27,2 ± 2,8 atau berkisar antara 24,4-30,0 m. Nilai Penting (INP) tertinggi di habitat A.ursinus pada tingkat pohon adalah Ficus benjamina (66,6%), Garuga floribunda (30,4%) dan Cananga odorata, Palaqium obovatum (30,3%). Sedangkan vegetasi tingkat tiang Phaleria capitata (40,8%), Diospyros sp. (37,7%) dan Dracontomelon mangiferum (34,7%). Jenis-jenis tersebut memegang peranan penting dalam membentuk habitat jelajah A.ursinus. Kata kunci: Kuskus Beruang (Ailurops ursinus), Bioekologi, Satwa Liar